Optimal sizing of distributed generation by using quantum-inspired evolutionary programming - Zuhaila, Mat Yasin; Titik Khawa, Abdul Rahman, Prof. Dr.; Ismail, Musirin, Dr.; Siti Rafidah, Abd Rahim (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/